TRADE AND CULTURAL EXCHANGE ALONG THE SILK ROAD: A HISTORICAL STUDY - Bhanumathi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Extending from East Asia to the Mediterranean, it was a channel of transportation of goods, ideas, technologies, religions and artistic traditions. The paper will look into the historical importance of the silk road as far as is concerned, using secondary literatures and historical sources. The research project brings out the intercourse effect of economic activities on intercultural relations and how interrelations develop global civilization. Patterns of trade and cultural diffusion are investigated statistically with the use of statistical description and hypothesis testing.